Characterization of a thermophilic and glucose-tolerant GH1 β-glucosidase from hot springs and its prospective application in corn stover degradation - Huang, Yu-Ying; Lv, Zhi-Hua; Zheng, Hong-Zhao; Zhu, Qian; Liu, Meng-Ting; Sang, Peng; Wang, Fei; Zhu, Dan; Xian, Wen-Dong; Yin, Yi-Rui (Frontiers in Microbiology, 2023)
β-Glucosidase serves as the pivotal rate-limiting enzyme in the cellulose degradation process, facilitating the hydrolysis of cellobiose and cellooligosaccharides into glucose. However, the widespread application of numerous β-glucosidases is hindered by their limited thermostability and low glucose tolerance, particularly in elevated-temperature and high-glucose environments. This study presents an analysis of a β-glucosidase gene belonging to the GH1 family, denoted lqbg8, which was isolated from the metagenomic repository of Hehua hot spring located in Tengchong, China. Subsequently, the gene was cloned and heterologously expressed in E. coli BL21(DE3). Post expression, the recombinant β-glucosidase (LQBG8) underwent purification through a Ni affinity chromatography column, thereby enabling the in-depth exploration of its enzymatic properties. LQBG8 had an optimal temperature of 70 ℃ and an optimum pH of 5.6. LQBG8 retained 100% and 70% of its maximum activity after 2-h incubation periods at 65 °C and 70 °C, respectively. Moreover, even following exposure to pH ranges of 3.0-10.0 for 24 h, LQBG8 retained approximately 80% of its initial activity. Notably, the enzymatic prowess of LQBG8 remained substantial at glucose concentrations of up to 3 M, with a retention of over 60% relative activity. The kinetic parameters of LQBG8 were characterized using cellobiose as substrate, with Km and Vmax values of 28 ± 1.9 mg/mL and 55 ± 3.2 μmol/min/mg, respectively. Furthermore, the introduction of LQBG8 (at a concentration of 0.03 mg/mL) into a conventional cellulase reaction system led to an impressive 43.7% augmentation in glucose yield from corn stover over a 24-h period. Molecular dynamics simulations offered valuable insights into LQBG8's thermophilic nature, attributing its robust stability to reduced fluctuations, conformational changes, and heightened structural rigidity in comparison to mesophilic β-glucosidases. In summation, its thermophilic, thermostable, and glucose-tolerant attributes，render LQBG8 ripe for potential applications across diverse domains encompassing food, feed, and the production of lignocellulosic ethanol.